1998
DOI: 10.1183/09031936.98.11040912
|View full text |Cite
|
Sign up to set email alerts
|

Expression of plasminogen activator inhibitors type-1 and type-2 in the mouse lung after administration of crystalline silica

Abstract: Altered expression of plasminogen activator inhibitors (PAIs) is of potential relevance to the process of lung fibrosis. To clarify the involvement of PAIs in interstitial lung diseases, we examined whether alterations in PAI-1 and PAI-2 were induced in response to a single intratracheal administration of a fibrosing dose of crystalline silica in mice (5 mg x animal(-1)). The time course of changes in PAI activity and PAI-1 protein were characterized in bronchoalveolar lavage fluid (BALF) and changes in PAI-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…uPA mRNA levels displayed a rapid and marked upregulation after silica treatment, followed by a progressive decrease later on (28). Comparable changes have been found in the expression of plasminogen activator inhibitors type 1 and type 2 during the evolution of silicosis in mice lungs (29). These are important observations, because plasminogen activator appears to play a role in limiting fibrosis by disassembling the fibrin and procollagen scaffolds, and also by enhancing MMP activation.…”
Section: Discussionmentioning
confidence: 74%
“…uPA mRNA levels displayed a rapid and marked upregulation after silica treatment, followed by a progressive decrease later on (28). Comparable changes have been found in the expression of plasminogen activator inhibitors type 1 and type 2 during the evolution of silicosis in mice lungs (29). These are important observations, because plasminogen activator appears to play a role in limiting fibrosis by disassembling the fibrin and procollagen scaffolds, and also by enhancing MMP activation.…”
Section: Discussionmentioning
confidence: 74%
“…PAI-3 regulates enzymes involved in fertilization rather than lung tissue fibrosis, whereas altered expression of both PAI-1 and PAI-2 is of potential relevance to the process of lung fibrosis (24,25). Although PAI-2 exhibits inhibitory activity toward tPA and uPA (26,27), the efficiency of PAI-2 is 20-to 100-fold less than what is observed for PAI-1 (28).…”
Section: Ast Cells Are Multifunctional Effector Cells That Partic-mentioning
confidence: 86%
“…Silicosis is an occupational lung disease caused by inhalation of crystalline silica dust and features inflammation and scarring in the form of nodular lesions in the upper lobes of the lungs. Lardot et al (128) reported that a single intratracheal administration of a fibrosing dose of crystalline silica in mice increased PAI-1 activity and protein levels in macrophages and neutrophils from BALF, associated with an induction of PAI-1 and PAI-2 mRNA in lung tissue. Sustained upregulation of PAI-1 and PAI-2 mRNAs was still noted in lung tissue of these animals 1 month after silica treatment.…”
Section: Pai-1 and Lung Fibrosis: Animal Modelsmentioning
confidence: 99%